Fast mechanochemical combustion synthesis of nanostructured vanadium boride by a magnesiothermic reaction. Issue 1 (January 2016) - Hassanzadeh-Tabrizi, S.A.; Davoodi, Danial; Beykzadeh, Ali Asghar; Salahshour, Saman
Abstract: Vanadium boride (VB) nanopowder was synthesized by mechanochemical combustion method in a high-energy ball mill. The synthesized powders were analyzed by X-ray diffraction (XRD), differential thermal analysis (DTA), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The results indicated that the reaction between Mg, V2 O5 and B2 O3 mixture was highly exothermic and operated in a combustion mode. XRD analysis showed that the vanadium boride was formed after 100 min milling time without any further heat treatment. The TEM results showed that the obtained vanadium boride aggregates were composed of nano-sized primary particles with a mean diameter of about 36 nm.